Microbiological identification of pathogens in water from educational centers in Norte de Santander - Soto , Javier Andrés; Martínez-Marciales, Karen Piedad (Revista Cuidarte, 2025)
Highlights • Water is food, which is why it is necessary to consume it daily, as it allows us to stay hydrated for developing vital functions. • Water contamination is caused by microbiological, physical, and chemical characteristics. • For proper water care, it is necessary to verify the storage conditions. • It is always necessary to know the quality and safety of the water; this is done through periodic microbiological and physicochemical analyses that allow the detection of any non-compliance with the criteria of suitability for human consumption. Introduction: Water is an essential resource for survival, and therefore, its quality and safety must be a priority, especially for susceptible population groups. Objectives: To determine the presence of mesophilic aerobes, coliforms, and Pseudomonas in drinking water in schools from three municipalities of Norte de Santander. Materials and Methods: Maintenance personnel were inquired about water storage. Samples from different sources were collected and processed using the membrane filtration method to identify aerobic mesophilic bacteria, E. coli, coliforms, Pseudomonas spp., and Salmonella spp. following the technical standards established for each microorganism. Results: Mesophilic bacteria growth was identified in 77.50% of the samples, total coliforms in 84.00%, fecal coliforms in 72.00%, and Escherichia coli in 21%. Pseudomonas spp. was also identified in 73.00% of the samples and Salmonella spp. in 10.50%. Discussion: These findings reflect non-compliance with current regulations due to the presence of indicator organisms such as mesophiles and the indicator par excellence in water quality: coliforms, a fact that is ratified by the presence of Pseudomonas spp. and Salmonella spp. Conclusions: The presence of these microorganisms is associated with failures in the water purification process, which allows us to expose the need for corrective actions to guarantee the microbiological quality of water and ensure health. How to cite this article: Soto Javier Andrés, Martínez-Marciales Karen Piedad. Microbiological identification of pathogens in water from educational centers in Norte de Santander. Revista Cuidarte. 2025;16(1):e4052. https://doi.org/10.15649/cuidarte.4052